1980
DOI: 10.4315/0362-028x-43.8.656
|View full text |Cite
|
Sign up to set email alerts
|

Sample Position Effects on Moisture Analyses by a Microwave Oven Method

Abstract: Microwave ovens are useful in rapid moisture analysis systems and preliminary drying to prepare analytical samples. Because of uneven heat distribution reported previously, we compared effects of 20 sample locations in a microwave oven cavity on moisture percentages of six meat and three milk samples. The same two hot spots (high moisture percentages) were noted for meat and milk samples. Microwave moisture percentages did not differ from standard oven drying results for meat samples but were higher (P &lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated the application of microwave drying to milk and dairy products (Thomasow, 1985;Dzurec and Beptide, 1989;Dzurec, 1991;Marquez et al, 1993;Marquez, 1995 andHurskar andVahcic, 1999). Several authors identified areas of caution in the use of microwave method such as splattering of sample and subsequent loss of solids, sample burning, differences in results from one microwave oven to the next (even when the same analysis conditions were used) and differences in results due to differences of dielectric properties of sample (Lee and Latham, 1976;Hayward andKropf, 1980 andBarbano andDellaValle, 1984). However, little attention has been given to this method in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the application of microwave drying to milk and dairy products (Thomasow, 1985;Dzurec and Beptide, 1989;Dzurec, 1991;Marquez et al, 1993;Marquez, 1995 andHurskar andVahcic, 1999). Several authors identified areas of caution in the use of microwave method such as splattering of sample and subsequent loss of solids, sample burning, differences in results from one microwave oven to the next (even when the same analysis conditions were used) and differences in results due to differences of dielectric properties of sample (Lee and Latham, 1976;Hayward andKropf, 1980 andBarbano andDellaValle, 1984). However, little attention has been given to this method in Egypt.…”
Section: Introductionmentioning
confidence: 99%